Digitalisasi ASMAN TOGA dengan Pemanfaatan QR Code untuk Pendataan Jenis-jenis Tanaman - Oktavina Tirza Dinda Pratiwi, Natasya; Husniyyah Husniyyah; Ul Hikmah, Dhiya; Wiranti Meisufi, Ruro; Prasitha Lisyanti, Norrencia; Febrianita, Roziana (Jurnal Nusantara Berbakti, 2024)
Independent Care of Family Medicinal Plants (ASMAN TOGA) is a new innovation for the community in Gondek Village, Mojowarno District, Jombang Regency. However, currently the ASMAN TOGA land has not been managed optimally. Many villagers do not understand the types, characteristics, and utilization of family medicinal plants in the park. Previously, the introduction of medicinal plants was done manually with information boards that only provided a little information about the benefits of the plants. This study discusses digitalization techniques that can be applied to improve access to technology and information for the local community. The implementation is carried out using several methods, namely analysis, planning, implementation, delivery methods, evaluation and monitoring of results, and publication of results. The result of this activity is the discovery of a way to obtain more detailed information about the collection of medicinal plants in ASMAN TOGA by utilizing a digital information system in the form of a QR-Code. It is hoped that the implementation of this system can increase the efficiency of education and make it easier for the community to utilize medicinal plants in the ASMAN TOGA park.